2003
DOI: 10.1128/mcb.23.6.2068-2082.2003
|View full text |Cite
|
Sign up to set email alerts
|

The STE20 Kinase HGK Is Broadly Expressed in Human Tumor Cells and Can Modulate Cellular Transformation, Invasion, and Adhesion

Abstract: HGK (hepatocyte progenitor kinase-like/germinal center kinase-like kinase) is a member of the human STE20/mitogen-activated protein kinase kinase kinase kinase family of serine/threonine kinases and is the ortholog of mouse NIK (Nck-interacting kinase). We have cloned a novel splice variant of HGK from a human tumor line and have further identified a complex family of HGK splice variants. We showed HGK to be highly expressed in most tumor cell lines relative to normal tissue. An active role for this kinase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
136
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(144 citation statements)
references
References 55 publications
8
136
0
Order By: Relevance
“…In Tao-1 (D168A) protein, aspartate 168 is replaced by alanine. This amino acid substitution renders the kinase domain nonfunctional (53), and the resulting kinase-defective protein is predicted to act as a dominant-negative (54). Fortunately, females carrying tao-1(D168A) were able to lay eggs.…”
Section: Resultsmentioning
confidence: 99%
“…In Tao-1 (D168A) protein, aspartate 168 is replaced by alanine. This amino acid substitution renders the kinase domain nonfunctional (53), and the resulting kinase-defective protein is predicted to act as a dominant-negative (54). Fortunately, females carrying tao-1(D168A) were able to lay eggs.…”
Section: Resultsmentioning
confidence: 99%
“…MAP4K4 has been demonstrated to be overexpressed in various tumors, accelerating tumor cell transformation, promoting cell invasion and decreasing cell adhesion (12). Furthermore, the expression of MAP4K4 in CRC without lymph node metastasis is significantly lower compared with lymph node metastasis, indicating the role of MAP4K4 in promoting CRC proliferation, invasion and metastasis (13).…”
Section: Introductionmentioning
confidence: 91%
“…Dhillon et al (23) reported that MAP4K4 was able to activate p38 stress-activated protein kinase to enhance tumor proliferation. Wright et al (12) indicated that MAP4K4 was able to promote the malignant transformation, In addition, using siRNA technology, Collins et al (11) demonstrated that the knockdown of MAP4K4 was able to inhibit the invasion of ovarian cancer cells. In accordance with the aforementioned findings, the results of the current study showed that the expression levels of MAP4K4 were significantly elevated in the tumor and lymph nodes in CRC, indicating that MAP4K4 may promote the pathogenesis and development of tumors, and regulate tumor proliferation and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of MAP4K4 prevents TNF-a-induced insulin resistance in human skeletal muscle (29), and suppresses systemic inflammation by targeting macrophages (30). Moreover, MAP4K4 is overexpressed in diverse types of human cancer (31). Silencing of MAP4K4 by siRNA inhibits cancer cell invasion and migration of breast cancer, prostate cancer, ovarian cancer, and malignant melanoma (28).…”
Section: Introductionmentioning
confidence: 99%